2000
DOI: 10.1007/s001250050002
|View full text |Cite
|
Sign up to set email alerts
|

Relation between leptin and the regulation of glucose metabolism

Abstract: OverviewThe identification of the ob gene through positional cloning [1] and the discovery that its encoded protein, leptin, is essential for body weight homeostasis [2±4] have permanently altered the field of metabolic physiology. Over a 5-year period a substantial and rapidly changing body of knowledge has been created.Leptin, a 16 kDa circulating hormone produced and released primarily by adipocytes, exerts a regulatory control on food intake and energy expenditure [2±4]. Plasma leptin concentrations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 41 publications
6
79
0
2
Order By: Relevance
“…20 Except for body fat content itself serum leptin levels are under the control of a series of other hormonal and metabolic factors among which insulin probably plays a pivotal role. 21 The impairment of insulin secretion and/or sensitivity have been reported in patients with PA, however the reports concerning this topic are contradictory. Ishimori et al 16 found increased insulin sensitivity in patients with PA. On the other hand our recent study 17 and the study of Shamiss et al 14 demonstrated decreased insulin sensitivity in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 Except for body fat content itself serum leptin levels are under the control of a series of other hormonal and metabolic factors among which insulin probably plays a pivotal role. 21 The impairment of insulin secretion and/or sensitivity have been reported in patients with PA, however the reports concerning this topic are contradictory. Ishimori et al 16 found increased insulin sensitivity in patients with PA. On the other hand our recent study 17 and the study of Shamiss et al 14 demonstrated decreased insulin sensitivity in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 TNF-a has also been found to downregulate insulin-induced phosphorylation of insulin receptor substrate-1 (IRS-1) and to reduce insulin-dependent expression of GLUT-4. 40 Thus, it cannot be excluded that a complete absence of leptin action may impair the PKC signaling pathway as well as modulate glucose utilization. Obese rat: PMA effect on cardiac glucose metabolism D Morabito et al Overall, our results indicate that PKCa plays an important role in the regulation of myocardial glucose transport and it can be speculated that the impairment of this regulation in the heart of the obese Zucker rat reflects an early phase in cardiac pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, a major hormone secreted by white adipose tissue (WAT) (Zhang et al 1994), has been implicated in the regulation of body weight (Baskin et al 2001, Mantzoros 2001, glucose metabolism (Fruhbeck & Salvador 2000, Al-Daghri et al 2002, Ceddia et al 2002 and fertility (Brann et al 2002, Moschos et al 2002. Leptin null, Lep ob /Lep ob mice are obese, hyperphagic and insulin resistant (Coleman 1978).…”
Section: Introductionmentioning
confidence: 99%